2023
DOI: 10.1021/acs.jcim.3c00624
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Inhibition Mechanism of Xanthine Oxidoreductase by Oxipurinol: A Computational Study

Abstract: Xanthine oxidoreductase (XOR) is an enzyme found in various organisms. It converts hypoxanthine to xanthine and urate, which are crucial steps in purine elimination in humans. Elevated uric acid levels can lead to conditions like gout and hyperuricemia. Therefore, there is significant interest in developing drugs that target XOR for treating these conditions and other diseases. Oxipurinol, an analogue of xanthine, is a well-known inhibitor of XOR. Crystallographic studies have revealed that oxipurinol directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 225 publications
(348 reference statements)
0
4
0
Order By: Relevance
“…1 B and C. The Amber FF14SB force field 40 , 41 were used for proteins, and the TIP3P water model 42 , 43 was added for these systems. The parameterization protocol applied for the flavin adenine dinucleotide (FAD), molybdenum cofactor (MOA) and Fe 2 S 2 cluster (FES) have been described previously 44 , 45 .
Figure 1 ( A ) 3D structure of one subunit of XO, the close-up represents the XO’s active region.
…”
Section: Methodsmentioning
confidence: 99%
“…1 B and C. The Amber FF14SB force field 40 , 41 were used for proteins, and the TIP3P water model 42 , 43 was added for these systems. The parameterization protocol applied for the flavin adenine dinucleotide (FAD), molybdenum cofactor (MOA) and Fe 2 S 2 cluster (FES) have been described previously 44 , 45 .
Figure 1 ( A ) 3D structure of one subunit of XO, the close-up represents the XO’s active region.
…”
Section: Methodsmentioning
confidence: 99%
“…Calculating the average energies of nonbonded intermolecular interactions (Coulomb + van der Waals) with respect to specific reference residue(s) can provide insight into the role of individual residues. EDA has been proven effective in exploring MD simulations and QM/MM calculations for various protein systems. EDA was calculated using the AMBER-EDA code on the precatalytic stage of the polymerization reaction by the WT and Y432S systems. The analysis was run on 25,000 snapshots of the last 500 ns of the MD simulations.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the computational efficiency of MM/GBSA, several studies have shown that this method results in comparable or even more accurate data in ranking ligand affinities compared to the molecular mechanics/Poisson–Boltzmann surface area (MM/PBSA). The offset and surface tension default values were used to correct the nonpolar contribution to the solvation free energy, and the salt concentration in the GB equation was set to 150 mM. Previous studies have shown that the MM/GB­(PB)­SA can satisfactorily compare the relative ligand-binding affinities, particularly when dealing with similar ligands. Since the only difference between the Matched and MM5 is a C to G and G to C mutations in the fifth position of the ligand (t-DNA and nt-DNA, respectively) from the PAM, the entropic effect is not expected to be highly determinant.…”
Section: Methodsmentioning
confidence: 99%